Descemet membrane endothelial keratoplasty (DMEK) adoption, surgical barriers, and graft customization preference among corneal surgeons: A cross-sectional survey - Abdullrahman Mohammed Alshehri; José Vargas; Mohammed Almutlak; Rafah Fairaq; Sami T. Hameed; Halla Alabdulhadi; Sara AlHilali; Mohammed M. Abusayf; Halah Bin Helayel (PLoS ONE, 2026)
Objective To assess surgeon preferences, challenges, and graft-size customization practices in Descemet membrane endothelial keratoplasty (DMEK), and to explore their association with surgical confidence and adoption. Methods and analysis A cross-sectional, 22-item online survey was distributed to corneal surgeons to evaluate surgical experience, preferences, graft-size customization practices, and challenges related to DMEK adoption. A total of 55 complete responses were analyzed. Categorical variables were summarized as frequencies and percentages. Multiple-response items were analyzed independently. Selected variables were grouped into clinically meaningful categories. Exploratory subgroup analyses were performed based on DMEK case volume, and associations were assessed using Fisher’s exact test. Results A total of 55 participants completed the survey, of whom 47 (85.45%) had performed DMEK. Most participants were male (44, 80.0%) and aged 30–39 years (24, 43.63%). Customized graft sizing was used by 35 (74.47%) participants, and 36 (76.60%) reported that it influenced surgical decision-making or outcomes. Graft unfolding and preparation were the most challenging steps, with 27 (57.45%) and 24 (51.06%) participants reporting moderate to high difficulty, whereas patient selection was generally less difficult (28, 59.57% reporting no difficulty). Higher competence was reported for Descemetorhexis (29, 61.70%) and tissue selection (27, 57.45%), while lower competence was observed for graft unfolding (15, 31.91%). Hands-on and supervised learning methods were most valued, including wet-lab training (32, 68.09%) and one-on-one operating room training (34, 72.34%). Increasing experience was associated with improved performance but was not statistically significant. Conclusion DMEK adoption is influenced by both technical complexity and training exposure. While surgeons demonstrate confidence in foundational steps, graft preparation and unfolding remain key challenges. Structured hands-on training and supervised experience appear critical to improving surgical confidence and may support broader adoption of DMEK.